Uncanny urges : the familiar made strange : an exegesis presented in partial fulfilment of the requirements for the degree of Master of Fine Arts at Massey University, Wellington, New Zealand - Brown, Adi (Massey University, 2013)
My research is centred on examinations of the uncanny. I am interested in strategies of the uncanny and the fetish, both Surrealist strategies and how these strategies create psychologically compelling images and objects. I perceive the uncanny in my work as the familiar made strange through eccentric juxtapositions of every day materials, objects and images. Through a diverse range of artists such as Pat Brassington, Sarah Lucas, Louise Bourgeois and Hans Bellmar I have explored key strategies of the uncanny to locate my own practice. I also draw theoretically from the works of Sigmund Freud, Nicholas Royle, Julia Kristeva and W.D. Winnicott. Methods of play are utilised to examine the possibility of an uncanny aesthetic through a process of bricolage whereby photographs and sculptural forms are constructed from various everyday materials available or on hand. Through this method I investigate how photographs and sculpture can operate as uncanny or fetishistic stand-ins for the body, which is always absent although a primary referent for my work.
Keywords: Adi Brown; The uncanny (Psychoanalysis); Installation art; Criticism and interpretation